Empowering youth Muslim tourists: a guide to halal food literacy - Zaki, Syifa' Bawazir; Md Sawari, Siti Salwa (Korint Yayincilik, 2024)
Muslim consumers face a multitude of challenges in securing halal food, especially young tourists traveling abroad. Limited research explores their halal food literacy, hindering informed decision making. This quantitative study addresses this gap by identifying the level of halal food literacy within this demographic. A total of 384 Malaysian youth Muslim tourists, analyzing data using IBM SPSS version 26. Descriptive analysis, t-tests, ANOVA, and multiple regression analysis were employed. This research provides valuable insights for authorities, including government bodies and regulatory institutions, to enhance halal food experiences for young Muslim tourists.